2010
DOI: 10.1002/aqc.1071
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and status of medicinal leeches (genus Hirudo) in the Western Palaearctic: anthropogenic, ecological, or historical effects?

Abstract: ABSTRACT1. Distribution and status of medicinal leeches were re-considered in the light of the new taxonomy recognizing four Western Palaearctic species: Hirudo medicinalis, Hirudo verbana, Hirudo orientalis and Hirudo troctina.2. Recent records and new data obtained on expeditions to Ukraine, Russia, Azerbaijan, Kazakhstan, Uzbekistan and the Western Balkans were mapped to obtain an up-to-date overview of the distribution.3. Three hypotheses explaining the current ranges of all Hirudo species were tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Recently, it was suggested that most likely fast and efficient dispersal of medicinal leeches occurs by their mammalian hosts, for example cattle, as vectors of leech transfer between water reservoirs (Utevsky et al 2010;Trontelj & Utevsky 2012). Our study suggests that birds may play an important role in spreading of medicinal leech.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Recently, it was suggested that most likely fast and efficient dispersal of medicinal leeches occurs by their mammalian hosts, for example cattle, as vectors of leech transfer between water reservoirs (Utevsky et al 2010;Trontelj & Utevsky 2012). Our study suggests that birds may play an important role in spreading of medicinal leech.…”
Section: Discussionmentioning
confidence: 60%
“…Projecting the nesting area of the western marsh harrier over the distribution range of the leech shows that they overlap to a great extent. Such great overlap is not observed for the nesting area of Eurasian coot, mute swan and black-headed gull (Cramp & Simmons 1977;Minelli 2010;Utevsky et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buczyńsky et al (2014) suggest that nests may be important secondary habitats for medicinal leeches, but more observations in aquatic ecosystems, where natural leech populations occur, are necessary to support this hypothesis. These observations indicate that man-made losses of habitat could be also responsible for the demise of some populations of H. medicinalis (Grosser 2004;Elliott and Kutschera 2011;Elliott and Dobson 2014;Utevsky et al 2008Utevsky et al , 2010Kovalenko and Utevsky 2012).…”
Section: Discussionmentioning
confidence: 99%
“…8A, B). It is now rare throughout Western Europe, and endangered in many countries (Wells and Coombes 1987;Utevsky et al 2008Utevsky et al , 2010Kovalenko and Utevsky 2012;Petrauskiené et al 2011;Westendorff et al 2008;Sawyer 2013aSawyer , 2013bUtevsky 2005, 2012).…”
Section: Discussionmentioning
confidence: 99%